PERAN MEDIASI QUALITY OF WORK LIFE DALAM HUBUNGAN ANTARA KOMPENSASI FINANSIAL, DIGITAL FATIGUE, DAN TURNOVER INTENTION - Restika Putri Fajar Sari; Tri Kartika Pertiwi; G. Oka Warmana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The increasing rate of turnover intention in the digital transformation era encourages organizations to better understand the factors influencing employees' intention to leave, particularly those related to financial compensation, digital fatigue, and quality of work life. This study aims to examine the effects of financial compensation and digital fatigue on turnover intention with quality of work life serving as a mediating variable. A quantitative approach was employed using a survey of 88 employees. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through measurement model and structural model assessments to evaluate both direct and indirect relationships among variables. The findings indicate that financial compensation and digital fatigue do not have a significant direct effect on turnover intention; however, both variables significantly influence quality of work life. Furthermore, quality of work life has a significant effect on turnover intention and mediates the relationships between financial compensation, digital fatigue, and turnover intention. These findings suggest that turnover intention is shaped by more complex mechanisms than the direct effects of compensation and digital fatigue alone. Therefore, organizations should implement integrated strategies by improving compensation systems, reducing digital workload, and enhancing employees' quality of work life to strengthen employee retention and sustain organizational performance. ABSTRAK Tingginya tingkat turnover intention pada era transformasi digital mendorong organisasi untuk memahami berbagai faktor yang memengaruhi keinginan karyawan meninggalkan perusahaan, khususnya yang berkaitan dengan kompensasi finansial, digital fatigue, dan quality of work life. Penelitian ini bertujuan menganalisis pengaruh kompensasi finansial dan digital fatigue terhadap turnover intention dengan quality of work life sebagai variabel mediasi. Penelitian menggunakan pendekatan kuantitatif dengan metode survei terhadap 88 karyawan. Data dianalisis menggunakan Structural Equation Modeling–Partial Least Squares (SEM-PLS) melalui tahapan pengujian model pengukuran dan model struktural untuk menguji hubungan langsung maupun tidak langsung antarvariabel. Hasil penelitian menunjukkan bahwa kompensasi finansial dan digital fatigue tidak berpengaruh langsung secara signifikan terhadap turnover intention, tetapi keduanya berpengaruh signifikan terhadap quality of work life. Quality of work life juga terbukti berpengaruh signifikan terhadap turnover intention sekaligus memediasi hubungan antara kompensasi finansial dan digital fatigue dengan turnover intention. Temuan ini menunjukkan bahwa turnover intention dipengaruhi oleh mekanisme yang lebih kompleks dibandingkan pengaruh langsung faktor kompensasi maupun kelelahan digital. Oleh karena itu, organisasi perlu mengembangkan strategi yang terintegrasi melalui pengelolaan sistem kompensasi, pengurangan beban kerja digital, dan peningkatan quality of work life untuk memperkuat retensi karyawan serta menjaga keberlanjutan kinerja organisasi.